Determining the Opinions of Classroom Teachers and Classroom Teacher Candidates Regarding the Education They Received Before Service - Yaşar Çelik (Foxton Books, 2022)
In this study, it is aimed to reveal the contributions of the educational activities carried out in the primary school teaching undergraduate program in preparation for the profession, the problems encountered and potential solution. ‎This research is a qualitative study based on case study design. An easily accessible sampling technique was used in determining the cohortof the study. The working group consists of classroom teachers who work in official primary schools affiliated to the Ministry of National Education and students who study in classroom teaching in the 4th grade in the spring semester of the 2019-2020 academic year. 21 teachers and 36 teacher candidates participated in the study. The research data were obtained using a semi-structured interview form. Descriptive analysis was used in dataprocessing. In the research, it was concluded that the practices in classes and schools, extracurricular activities, studies for using instructional technologies, knowledge and skills about school-family cooperation and school management are not sufficient in terms of popularizing and practicing the profession. Based on these results, suggestions were made to choose teachers from among those who like the profession, to include more applied studies in terms of gaining skills, to use teaching technologies more in faculties, to increase the number and duration of school applications.